Design of Quasi-Elliptic Bandpass Filter for Substrate Integrated Waveguide (SIW) Using Cross Coupling Technique - Muhajir Mustapa; ZahrilAdha Zakaria; Noor Azwan Shairi (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper proposes a quasi-elliptic band pass filter in substrate integrated waveguide (SIW) by using cross coupling technique to produce transmission zeros (TZs) at both side. Finally, a fourth pole SIW quasi-elliptic filter at 5.75 GHz is designed in single layer substrate. Simulation results show that the filter has a center frequency of 5.75 GHz with the bandwidth of 100 MHz. The minimum insertion loss in the passband is 0.3 dB, and the return loss is better than 20 dB. Due to the TZs, the SIW filter has rapid transition performance at both lower and upper sidebands, good selectivity is achieved, while the SIW filter presents a very compact implementation and goodspurious rejection.